Equine-Assisted Therapy in South Africa: A Scoping Review of Applications and Effectiveness - Daniel Lesiba Letsoalo; Martine Bronwyn Menoe; Mahlatsi Venolia Semenya (E-Journal of Humanities, Arts and Social Sciences)
Equine-assisted therapy (EAT) has gained interest as an alternative treatment method. It shows promise in treating various physical, neurological, and mental conditions. South Africa, a country with many of these conditions, has introduced EAT as an alternative treatment in recent years. However, its effectiveness and the populations it benefits the most are still unclear. Therefore, the purpose of this study was to systematically map the existing literature on EAT to determine the populations where it is applied most and its effectiveness. Arksey and O’Malley’s methodology framework was followed to perform a scoping review. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR) guidelines were used for reporting, transparency and consistency. EBSCOHost (Academic Search Ultimate, APA PsycInfo), CINAHL with full text, Global Health, MEDLINE, Sabinet African Journals, and Google Scholar databases were searched and complemented by a freehand search of Google. Coverage of EAT was assessed in studies published between 2006 and 2024. The findings showed that EAT is commonly applied in populations with mental, neurological, and physical disabilities, and it resulted in positive treatment outcomes. The study suggests the importance of raising awareness and providing psychoeducation about EAT to the public. The study also contributes to the understanding of the applications and effectiveness of EAT, connecting with allied professions and providing evidence-based recommendations. Furthermore, the findings highlight the potential of EAT as a valuable therapeutic intervention and underscore the need for a continuous review of alternative treatment modalities, particularly emerging ones like EAT, in South Africa.